Validating Pupils’ Behaviour Intention to Use E-Book Technology in their Learning - Elyazgi, Moamar (International Journal of Engineering and Technology, 2018)
The purpose of this study was to develop and validate a new learning environments instrument designed to aid investigators and practitioners in measuring and researching the pupilsâ€™ behaviour intention to use e-book technology. The use of e-book technology in schools is now ubiquitous, but the effectiveness on the learning environment has mixed results. This study intends to investigate factors affecting pupilsâ€™ behavioural intentions to use the e-book technology. Integrating Child Computer Interaction (CCI) factors such as usability and interface with the Technology Acceptance Model (TAM) factors such as Perceived Enjoyment (PE),Â Perceived Ease of Use (PEOU), Perceived Usefulness (PU) and Behaviour Intention (BI). Using e-book technology acceptance survey was developed, field-tested with 40 pupils from school aged 10-17 yearsÂ and then validated. The proposed questionnaire has 33 items allocated to six scales: (1) Usability; (2) interface; (3) Perceived Enjoyment; (4) Perceived Ease of Use; (5) Perceived Usefulness and (6) Behaviour Intention. The proposed questionnaire was administered to pupils in the schools. Six experts in the field of computer science, information system and technology to justify it, especially in relation to the elements of each concept, assessed content validity or face validity of the questionnaire. Then alpha reliability, convergent validity and discernment validity have been calculated in this study. Â Â The questionnaire of e-book technology acceptance has strong evaluative and discriminative properties and can be used with confidence to measure the e-book acceptance for pupils.Â Â